Structural, optical, and magnetic characterization of spinel zinc chromite nanocrystallines synthesised by thermal treatment method - Gene, Salahudeen A.; Saion, Elias; Shaari, Abdul Halim; Ahmad Kamarudin, Mazliana; Al-Hada, Naif Mohammed; Kharazmi, Alireza (Hindawi Publishing Corporation, 2014)
The present study reports the structural and magnetic characterization of spinel zinc chromite (ZnCr2O4) nanocrystallines synthesized by thermal treatment method. The samples were calcined at different temperatures in the range of 773 to 973 K. Polyvinylpyrrolidone was used to control the agglomeration of the nanoparticles. The average particle size of the synthesized nanocrystals was determined by powder X-ray diffraction which shows that the crystallite size increases from 19 nm at 773 K to 24 nm at 973 K and the result was in good agreement with the transmission electron microscopy images. The elemental composition of the samples was determined by energy dispersed X-ray spectroscopy which confirmed the presence of Zn, Cr, and O in the final products. Fourier transform infrared spectroscopy also confirmed the presence of metal oxide bands for all the samples calcined at different temperature. The band gap energy was calculated from UV-vis reflectance spectra using the Kubelka-Munk function and the band gap energy of the samples was found to decrease from 4.03 eV at 773 K to 3.89 eV at 973 K. The magnetic properties were also demonstrated by electron spin resonance spectroscopy, the presence of unpaired electrons was confirmed, and the resonant magnetic field and the of the calcined samples were also studied.